1988
DOI: 10.1148/radiographics.8.1.3353531
|View full text |Cite
|
Sign up to set email alerts
|

Gd DTPA. Clinical efficacy.

Abstract: Both the diagnostic accuracy and sensitivity of the MRI diagnosis of central nervous system neoplasms appear to be improved by the administration of a paramagnetic contrast agent, Gd DTPA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…All samples were obtained within approximately a 4- to 8-hour period from the time of contrast administration to the moment of tissue collection and previous reports suggest that relative changes in concentrations of Gd in tissue should be minimal during this period (30, 37). Previous imaging literature also suggests that Gd is rapidly cleared from blood and because the tissue was obtained a minimum of 4 hours after the administration of Gd, we surmise that Gd present predominantly accumulated in the extravascular space (47, 48). Finally, it is possible that a decrease in the fluorescence signal from PpIX as a result of organic degradation processes could have occurred, but not so for Gd, which is a stable metal.…”
Section: Discussionmentioning
confidence: 55%
“…All samples were obtained within approximately a 4- to 8-hour period from the time of contrast administration to the moment of tissue collection and previous reports suggest that relative changes in concentrations of Gd in tissue should be minimal during this period (30, 37). Previous imaging literature also suggests that Gd is rapidly cleared from blood and because the tissue was obtained a minimum of 4 hours after the administration of Gd, we surmise that Gd present predominantly accumulated in the extravascular space (47, 48). Finally, it is possible that a decrease in the fluorescence signal from PpIX as a result of organic degradation processes could have occurred, but not so for Gd, which is a stable metal.…”
Section: Discussionmentioning
confidence: 55%
“…We are aware of the limitations imposed on this study by the relatively low number of cases. Furthermore, variations in treatment and duration of treatment prior to MR imaging could have altered the blood brain barrier, signal intensity, degree of peritumoral edema, mass effect, and the degree of contrast enhancement 18 . These results may also be biased by the large number of meningiomas in the neoplastic group; however, the preponderance of meningiomas in other studies of intracranial neoplasia in dogs and cats suggests that this is not unrealistic.…”
Section: Discussionmentioning
confidence: 99%
“…The parameter values for the 3D FLASH sequence were 35/5,45" flip angle, and RF spoiling with an increase of 1 17.5" in the phase increment at each TR. (The 3D FLASH TR, TE, and flip angle were the same as those used for one of the RF-spoiled GRASS sequences studied in reference 9.) The parameter values for the 3D MP-RAGE sequence included a 180" RF prcparation pulse followed by a 300-msec delay and an ideal-spoiled FLASH acquisition sequence (10/4, 12" flip angle, 64 phase-encoding steps per sequence cycle with sequential phase-encoding order, and a 20-msec recovery period).…”
Section: S D (And Sdin Valuesmentioning
confidence: 99%
“…However, in some later clinical studies (6-8) that compared GD-enhanced 2D or 3D T1-weighted GRE sequences with conventional 2D T1-weighted SE sequences, it was found that the GRE images demonstrated inferior contrast enhancement for some lesions compared with SE images. Possible reasons for this inferior contrast behavior include ( a ) signal loss due to an increased sensitivity to susceptibility effects in the GRE sequence and ( b ) fundamental differences between the contrast behaviors of the SE and GRE techniques (6,(8)(9)(10). These results raise the question of whether there are fundamental limitations with GD-enhanced GRE imaging compared with conventional SE imaging, even though-based on the heavily T1-weighted image appearance that can be achieved with the GRE techniques-one might expect the contrast enhancement performance of the GRE techniques to be at least comparable to that of SE techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation